Reliability and construct validity of knowledge, attitude & practice (KAP) of medical doctors on smoking cessation guidelines - Shalihin, Mohd Shaiful Ehsan; Md Aris, Mohd Aznan; Nik Mohamed, Mohamad Haniki; Mohd Rus, Razman; Jamani, Nurjasmine Aida (2016)
Islam forbids everything that is harmful, and this applies to any forms of tobacco. Sadly, number of active smokers in Malaysia is increasing despite availability of stop smoking clinics and smoking cessation medications. Thus, the practice of the healthcare professionals involved in providing smoking cessation intervention using evidence-based guidelines needs to be assessed using validated assessment tool. This study aimed to develop and validate a questionnaire to assess the knowledge, attitude and practice of medical doctors based on national smoking cessation guidelines and factors contributing to the score. The 26 items consists of mixture of true/false choice questions; strongly agree/agree/ don’t know /disagree / strongly disagree response; and always/frequent/seldom/never response were created based on domain of 5A’s (ask, assess, advice, assist, arrange) and 5R’s (relevant, risks, rewards, roadblocks, repetitions) of the national stop smoking guidelines. The questionnaires were distributed to 141 medical doctors. Reliability was determined using Cronbach’s alpha for internal consistency while construct validity was assessed using factor analysis. A high degree of internal consistency was observed for this 26 items (Cronbach’s alpha = 0.824) and for practice subscale (Cronbach’s alpha 0.83). Subsequently, one item from knowledge subscale and practice subscale (poor inter-item correlations) were removed. Factor analysis extracted 7 meaningful components from this remaining 24 items, in which 3 components with least items were deleted due to overlapping subscale with other components, leaving 4 meaningful components, consist of (1st) practice ask, advice, assess (4 items) and practice 5R’s (6 items), (2nd) practice of assist and arrange for those willing to quit (2 items), (3rd) knowledge (2 items) and (4th) attitude (3 items). These final 17 items still demonstrate high internal consistency with Cronbach’s alpha of 0.832. This study indicates that this questionnaire is a reliable and valid tool to assess the knowledge, attitude and practice on stop smoking guidelines. Improvement can be made for attitude items in future.